Within, rather than against the state? How indigenous movements in Ecuador and Peru engage with elections - Lea Haiges; Christina Isabel Zuber (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
While indigenous movements often keep a deliberate distance from their states, political connections can be important to effect policy change. How do indigenous organizations navigate this challenge? This article analyses the electoral strategies of 19 indigenous organizations during elections in Ecuador and Peru. The analysis draws on an original data-set of organizational communication on social media, complemented with semi-structured interviews conducted during field work. We find that most organizations engage actively with elections. Aside from a more expected strategy of protesting election outcomes, they also call on followers to vote and actively mobilize in favor or against certain candidates, participating within, rather than against the state. An allied indigenous party (Pachakutik in Ecuador) does not explain organizations' engagement with elections per se, but it does affect the rationale for choosing one or the other strategy: organizational reasons dominated in Ecuador, while shared identity was most important in Peru.
urn:nbn:de:bsz:352-2-muafltj55uw2
Keywords: 320; indigenous movements; social movements; electoral campaign; socialmedia; Ecuador; Peru